SaaSDCS: softwareasaservice discovery and composition systembased existence degree. (2015) - Saouli, Hamza; Kazar, Okba; Benharkat, AÁ¯cha Nabila
Softwareasaservice (SaaS) is one of the most important delivery models for cloud computing technology. Recently, this model is widely produced, adopted, and used by organisations and particular consumers. The rapid adoption of SaaS model and the exponential growth in number and functionalities of the applications offered by cloud services providers led us to propose an automatic publication, discovery and composition system. The proposed system takes into consideration the main aspects of SaaS products: categorisation, functional, QoS and cloud attributes. We use these aspects to propose a complete SaaS description model. Then, we use it to propose service matchmaking algorithms for SaaS selection, composition and ranking based on a new concept called 'existence degree'. A prototypical implementation is conducted in order to evaluate our system. The obtained results demonstrate the effectiveness of the proposed system.